(untitled) (International Journal of Technology and Management Research, 2020)
The present study aims to examine the hospitality management education system in Ghana and report the initial findings of a qualitative research undertaken for an assessment of the hospitality education system. The views of graduates and students were gathered through in-depth interviews on the hospitality education that they have received. The findings of the study show that the curriculums used by hospitality students in the Polytechnics are overloaded with non-hospitality related subjects. Most of the interviewees felt that they have gained adequate theoretical knowledge and practical skills in the area of food production operation, food and beverage service with little practical knowledge in other subjects. The implication is if the current curricula run by departments of hospitality in the Polytechnics are not reviewed on timely bases, st hospitality management graduates from Polytechnics may not meet the needs of industries in this 21 century. Keywords: Training; hospitality management; education; qualitative research; curriculum.